2017
DOI: 10.1136/neurintsurg-2017-013150
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular management of aneurysms associated with spinal arteriovenous malformations

Abstract: Identification of a symptomatic aneurysm should be associated with clinical presentation pattern. Targeted obliteration of the aneurysm by embolization and/or surgery resulted in improvement of symptoms and stabilization of SAVM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…[1][2][3] Our study also demonstrated an excellent occlusion rate (100%) and good treatment outcomes (91%). Intradural venous drainage, noted in 53.8% 7 of the 13 patients in this study, was seen with variable frequency in previous studies (27.0% 2 to 74.5% 4 ). In this study, ALS scores were zero in all patients without intradural venous drainage except for 1 patient who had mild leg weakness caused by compressive myelopathy.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…[1][2][3] Our study also demonstrated an excellent occlusion rate (100%) and good treatment outcomes (91%). Intradural venous drainage, noted in 53.8% 7 of the 13 patients in this study, was seen with variable frequency in previous studies (27.0% 2 to 74.5% 4 ). In this study, ALS scores were zero in all patients without intradural venous drainage except for 1 patient who had mild leg weakness caused by compressive myelopathy.…”
Section: Discussionsupporting
confidence: 45%
“…5 Differentiation from other spinal vascular pathology, including SDAVF, is mandatory to localize the exact cause of presenting symptoms. 6,7 SEDAVFs can be categorized into 2 distinct presenting symptom patterns, depending on the involvement of the intradural vein. 8 With intradural venous reflux, they may mimic SDAVFs with symptoms of congestive myelopathy such as lower leg weakness and sphincter dysfunction.…”
mentioning
confidence: 99%
“…Aneurysms on the arterial feeders of the AVMs are known to be associated with an increased risk of rebleeding 21. They are usually considered as a target of embolization with cyanoacrylate or surgery 22. We reported in our series five patients with such aneurysms which were definitely occluded using particle embolization (figure 1).…”
Section: Discussionmentioning
confidence: 69%
“…ASA aneurysms are rare and are mainly located in the upper cervical segment (4,(79)(80)(81)(82). They are typically dissections and can be divided into isolated and flow-related types (83,84).…”
Section: Cervical Asa Aneurysmmentioning
confidence: 99%